Changes in Orthopedic Surgery at the Community Level - Lagoe Ronald; Murphy Mark; Littau Shelly (Journal of Current Scientific Research, 2021)
This perspective outlines how community orthopedic services adapted to shifting demands and constraints. It discusses scheduling, triage, infection control, and telemedicine adoption, and proposes metrics to track access and outcomes during system changes.
Keywords: Orthopedic Surgery